Hakmilik tanah GSA FELDA dan isu kelewatan pengeluarannya, kajian kes: tanah rancangan FELDA di negeri Johor - Low, Siong Khim (2007)
Legal ownership of land confers a sense of pride and achievement on rural people who were previously landless. The title deed confers a sense of security and is a proof of land ownership. Federal Land Development Authority or FELDA was established under the Land Development Ordinance 1956 with the aim of clearing up jungle land and developing into agricultural land for the settlement of rural people. It aims to raise the social economic status of the settlers and promise to give land to the landless. The settlers were initially accepted into the FELDA scheme as settlers occupying rural settlement holdings in expectation of titles, they wait with anxiety to receive the titles on completion of their loan obligation. The process of issuance of titles to settler involves various anthorities, who have to verify and validate relevant material facts before the State Government officially confers the legal title to the settler. The parties involved include the settlers themselves, FELDA management, the respective District Land Office, Director of Land and Mines Department, Survey and Mapping Department and also Licensed Land Surveyors appointed to carry out the survey of the lots allocated. This study is an attempt at elucidating the reasons for the delay in the processing of the application for the granting of title deed under the Land (Group Settlement Area) Act 1960, with special reference to the land schemes in the State of Johore, Malaysia. Data concerning the delay in the processing and registration of titles was summarized and evaluated at every pertinent level and the Government Departments concerned as well as the Land surveyors concerned. Information and data were compiled through detailed survey proformas as well as questionnaires and direct discussions with FELDA Authorities, relevant officers in all Government departments concerned and the Licensed Land Surveyors responsible for the surveying of the respective lots. Qualitative analysis was carried out establishing timelines as well as having detailed discussions on specific cases with all parties involved. All respondents’ perspective on the causes for the delay was also sought. The collated data was analyzed, tabulated and presented as tables and pie-charts for ease of comprehension. It is concluded that the causes for the delay are multifarious, commencing from the initial submission to the various levels of checking and verification before approval is given. In order to speed up the issuance of land title to the settler, various alternative were suggested including submission of accurate data of settler after close scrutiny by the FELDA management, increase in staff strength in district land office where many FELDA schemes are located, close coordination and cooperation between the parties involved, removal of bureaucracy, amendment to the process of gazetting under GSA, incorporation of the concept of field to finish in land survey and enhancement of computer registration of land titles.